Phyllosphere Fungi of Porang Leaf Blades Amorphophallus muelleri Blume (Araceae) in Lombok - Ahsanu Nadia; Sukiman Sukiman; Tri Mulyaningsih; Ernin Hidayati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The Porang plant is a native Indonesian plant that produces tubers and can live in shady places. In general, there are two types of porang planted by the community, namely A. muelleri and A. konjac. This study aims to identify phyllosphere fungi associated with porang plants and the presence of these phyllosphere fungi. By using the 10-1, 10-3 and 10-5 distribution method and the patch method. The results of the study successfully isolated 21 isolates of phyllosphere fungi identified into eleven genera: Aspergillus, Cunninghamella, Fusarium, Mortierella, Mucor, Myselia, Neurospora, Paecilomyces, Pythium, Rhizoctonia, and Verticillium, and phyllosphere fungi were found on the upper epidermis surface. The conclusion is that the presence of phyllosphere fungi is anatomically on the upper surface of the epidermis.